Visible light-promoted CO2 fixation with imines to synthesize diaryl α-amino acids. Issue 1 (December 2018) - Fan, Xinyuan; Gong, Xu; Ma, Mengyue; Wang, Rui; Walsh, Patrick
Abstract Light-mediated transformations with CO2 have recently attracted great attention, with the focus on CO2 incorporation into C–C double and triple bonds, organohalides and amines. Herein is demonstrated visible light -mediated umpolung imine reactivity capable of engaging CO2 to afford α-amino acid derivatives. By employing benzophenone ketimine derivatives, CO2 fixation by hydrocarboxylation of C=N double bonds is achieved. Good to excellent yields of a broad range of α, α–disubstituted α-amino acid derivatives are obtained under mild conditions (rt, atmospheric pressure of CO2, visible light). A procedure that avoids tedious chromatographic purification and uses sustainable sunlight is developed to highlight the simplicity of this method. Fixation of CO2 in organic molecules is an area of great interest due to the implications in sustainable chemistry. Here, the authors show a visible light-mediated hydrocarboxylation of ketimines with atmospheric CO2 to afford a number of α, α–diaryl α-amino acid derivatives.